Shear Stress Affects Biofilm Structure and Consequently Current Generation of Bioanode in Microbial Electrochemical Systems (MESs) - Yang, Jiawei; Cheng, Shaoan; Li, Chaochao; Sun, Yi; Huang, Haobin (Frontiers in Microbiology, 2019)
Shear stress is an important factor that affects the formation and structure of anode biofilms, which are strongly related to the extracellular electron transfer phenomena and bioelectric performance of bioanodes. Here, we show that using nitrogen sparging to induce shear stress during anode biofilm formation increases the linear sweep voltammetry peak current density of the mature anode biofilm from 2.37 ± 0.15 to 4.05 ± 0.25 A/m2. Electrochemical impedance spectroscopy results revealed that the shear-stress-enriched anode biofilm had a low charge transfer resistance of 46.34 Ω compared to that of the unperturbed enriched anode biofilm (72.2 Ω). Confocal laser scanning microscopy observations showed that the shear-stress-enriched biofilms were entirely viable, whereas the unperturbed enriched anode biofilm consisted of a live outer layer covering a dead inner-core layer. Based on biomass and community analyses, the shear-stress-enriched biofilm had four times the biofilm density (136.0 vs. 27.50 μg DNA/cm3) and twice the relative abundance of Geobacteraceae (over 80 vs. 40%) in comparison with those of the unperturbed enriched anode biofilm. These results show that applying high shear stress during anode biofilm enrichment can result in an entirely viable and dense biofilm with a high relative abundance of exoelectrogens and, consequently, better performance.